Polymorphism in FAE1gene paralogs of Brassica juncea associated with erucic acid content: Polymorphism in FAE1gene paralogs of Brassica juncea associated with erucic acid content - YASHPAL,; NAVINDER SAINI,; NAVEEN SINGH,; RAJENDRA SINGH,; SUJATA VASUDEV,; D K YADAVA, (Journal of Oilseeds Research, 2020)
Breeding for low erucic acid is a major objective to improve the edible oil quality in Brassica juncea. FAE1, theintron-less, 1521-bp gene encoding fatty acid elongase, genetically control the biosynthesis of erucic acid in oilseed Brassicas. The Brassica juncea being an amphidiploid, contains two paralogs of this gene (FAE1.1 and FAE1.2). Allelic variations in the gene such as SNPs and InDels are predominantly responsible for variability in erucic acid content in the seed, among the Brassica genotypes. The coding sequence of FAE1 gene paralogs were sequenced from low (LEA) and high (HEA) erucic acid genotypes which had a few SNPs that differentiated LAE and HEA genotypes. Two SNPs in FAE1.1 at position 591 and 1265 and one in FAE1.2 at 237, which led to a change in the recognition site of Hpy99I, BglII and MnlI restriction enzymes, respectively, converted into CAPS markers to differentiate LEA and HEA genotypes. The efficacy of these CAPS markers was found 100 per cent when validated in Brassica juncea, B. rapa and B. nigra genotypes and used in back-cross breeding. However, owing to functional complexity of CAPS in routine analysis; nucleotide sequence variability in the promoter region of FAE1 gene paralogs were expedited to develop simple PCR based markers. The upstream regions of FAE were sequenced from LEA cultivar Pusa Mustard30 and HEA cultivar Pusa Bold. A28-bp deletion in the promoter of FAE1.1 and a 340- bp insertion of a transposonlike element in the FAE1.2 gene promoter was discovered in LEA genotype in comparison to HEA. Markers based on these sequence variabilities in the promoter regions of FAE1.1 and FAE1.2 were found to completely co-segregate with the seed erucic acid content. These markers would be effectively used in marker assisted selection for development of low erucic acid cultivars in B. juncea.